2018
DOI: 10.1103/physrevd.98.123508
|View full text |Cite
|
Sign up to set email alerts
|

Deflection of light and time delay in closed Einstein-Straus solution

Abstract: We investigate strong lensing by a spherically symmetric mass distribution in the framework of the Einstein-Straus solution with positive cosmological constant and concentrate on the case of a spatially closed Universe (k = +1). We develop a method based on integration of differential equations in order to make possible the computation of light deflection and time delay. By applying our results to the lensed quasar SDSS J1004+4112, we find that the bending of light and time delay depend on wether the present v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Also the method has been applied to galactic halos, of which an excellent example is the Mannheim-Kazanas solution of conformal Weyl gravity [33][34][35]. For further insight into the use of the Rindler-Ishak method, see [36][37][38][39][40].…”
mentioning
confidence: 99%
“…Also the method has been applied to galactic halos, of which an excellent example is the Mannheim-Kazanas solution of conformal Weyl gravity [33][34][35]. For further insight into the use of the Rindler-Ishak method, see [36][37][38][39][40].…”
mentioning
confidence: 99%
“…In [16], Schucker used a similar method to estimate the bending angle for a lensing cluster at fixed redshift, and found that when a higher Λ was used, the bending angle decreased (table 4 in [16]), which appears to be in agreement with Rindler and Ishak's claim that Λ attenuates lensing. Guenouche et al [27] also used a similar formalism and reached the same conclusion. The decrease in bending angle was as much as 10% when Λ increased by 20%.…”
Section: Jcap02(2022)009mentioning
confidence: 55%
“…In addition, in both cases, the first-order contribution from the cosmological constant is negative, so that the cosmological constant Λ diminishes the bending (see also Ref. [9,55]). However, due to the different methods used to calculate the bending angle, this term is different in the two cases.…”
Section: Discussionmentioning
confidence: 94%